Türkiye'de dünden bugüne özel okullara bir bakış (gelişim ve etkileri) - Selçuk UYGUN (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In this research, the development of private schools, and its effects since Tanzimat (Reorganization) period in Turkey has been examined. Private schools, which are different from traditional school comprehension, developed after Tanzimat period, which is considered as becoming westernization, through leadership of foreign and minority groups. Private schools of foreign and minority groups had positive effects on feature improvement and modernization of Turkish education system. However, these schools have also harmful consequences because of their religious, political, economical, cultural, etc. structures, and their contrary activities to politics of goverment. Before Republic period, towards adverse consequences of these schools, goverment could not find any fundamental solution because its economic and political weakness. This fundamental solution is being reached after Turkish people national liberation war and complete its independent republic establishment. After Republicanism, especially first years of Republicanism, the schools of foreign and minority groups had been under supervision and inspection of goverment and their activity fields had been restrictive. From the foundation of Repuplic until 1960’s the development of private schools was steady. After 1960’s, there are proceedings at private schools activities and these proceedings, especially after 1980’s, accelerated in favor of private schools. Nowadays, from kindergarten to university, number of private schools that provide education-instruction in every level, increases every day and goverment is supporting these schools. Today, the students at private schools, that have been opened by the Turkish, are almost all Turkish. These schools are creating competitions in education, they are acquiring qualified education environments therefore the demands, and the popularity of these schools are getting higher as in the past